2017
DOI: 10.4317/jced.54129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the teaching program on the learning in knowledge and practice of osteonecrosis of the jaws produced by antireasorptives in dental students of the Principality of Asturias (Spain)

Abstract: BackgroundThis study aims to evaluate the influence of changes in the teaching contents on medication-related osteonecrosis of the jaw may have on the knowledge and the capacity for practical case resolution about this pathology.Material and MethodsA cross-sectional descriptive study was conducted through a survey divided into four sections: degree of means of knowledge acquisition, habitual practice and ability to solve clinical cases. The total number of respondents (n = 225) was divided into two groups: Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
4
10
0
2
Order By: Relevance
“…Almost 80% of the participants answered that they knew the bisphosphonates, similarly to the results of other studies (60% to 80%) (De Lima et al, 2015;Escobedo et al, 2017;Al-Eid et al, 2020;Al-Maweri et al, 2020;Almousa et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Almost 80% of the participants answered that they knew the bisphosphonates, similarly to the results of other studies (60% to 80%) (De Lima et al, 2015;Escobedo et al, 2017;Al-Eid et al, 2020;Al-Maweri et al, 2020;Almousa et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Although the need for dissemination of information about bisphosphonates and BAONJ for the dental community is evident, few studies have been directed to understand the knowledge of dental students and professionals about the subject, in In the present study males and females showed similar knowledge about bisphosphonates and BAONJ, similarly to the results of Escobedo et al (2017). The present sample was composed mainly by dental students and participants derived from private dental schools, in contrast to the sample studied by De Lima et al (2015).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In previously reported studies, in the evaluation of knowledge regarding the therapeutic indications for bisphosphonates, antiresorptive, or antiangiogenetic, osteoporosis was the most stated answer by participants followed by cancer treatment for bone metastases and multiple myeloma and osteogenesis imperfecta [ 13 , 33 , 34 , 37 ]. These previous reports verify the results of this survey that osteoporosis was the main therapeutic indication stated by the dentists, followed by cancer treatment of patients with metastatic bone tumors, multiple myeloma, and osteogenesis imperfecta and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…AAOMS, bisfosfanata bağlı çene osteonekrozunun (BRONJ) terimi ve antirezorptif ajan kaynaklı osteonekroz (ARONJ) terimi yerine; ilaca bağlı çene kemiği osteonekrozu (MRONJ) teriminin kullanılmasını önermiştir. [9][10][11] Bu değişim; antirezorptif ve antianjiogenik ilaç tedavisiyle ilişkili maksilla ve mandibulayı içeren osteonekroz olgularının artan sayısı ile desteklenmektedir. 12 Bu tanımına göre hastalar;…”
unclassified